The Implemented of the concept of amal online in UiTM Puncak Alam / Siti Aishah Mohd Zin - Mohd Zin, Siti Aishah (2019)
Amal online refers to the one of an approach by electronic payment or better-known as e-payment. It was capable to implement the payment process through the network internet in a simple way and fast without using the manual process. For example, Lembaga Zakat in Malaysia has been trying for several years to introduce Amal online in order to improve their collecting charity and improve their services. Thus, the objectives of this research are to explain the concept of Amal online, analyze the scholars view on Amal online and to purpose the model of Amal online that suitable to use in this generation. There are 51 respondents that participate in this research where all the respondents are students at MARA University of Technology Malaysia, Puncak Alam. This research analyzing is by using manual method. From the finding it can be said that the concept of Amal online is different with direct charity which is Amal online is collecting charity by electronic payment, the advantages and benefit is not only for Muslims and lastly Amal online is one of the charity’s platform. The scholars view on Amal online is permissible as long as to get the blessed from Allah. The model of Amal online is suitable to use in this generation because of it easier and useful to the donors. It is also suggested that holistic strategic approach is needed for this Amal online that to implemented in UiTM Puncak Alam. It is hope that the study can contribute to the implemented of Amal online in UiTM Puncak Alam.